SOSIALISASI MEMBANGUN KARAKTER MANDIRI GENERASI MUDA MELALUI PENDIDIKAN BERBASIS KEWIRAUSAHAAN - Putra Kaslin Hutabarat; Rifka Hadia Lubis (Universitas Pahlawan Tuanku Tambusai, 2022)
Community Service Activities (PKM) are based on phenomena that occur in the community related to the low independent character developed by the younger generation through entrepreneurial activities. Therefore, education is very important as a forum for developing the talent and potential of the younger generation to be able to create products that can be produced and sold to consumers. It is hoped that this activity will be able to move the character of the younger generation by approaching education and training on entrepreneurship. The method of implementing this activity is to provide educational outreach and entrepreneurship training through the production of Kremes bananas so that they can be used as income-generating products. This service is carried out for teenagers in the village of Siporas, Pinangsori District, Central Tapanuli Regency. The results of this activity are expected to be able to improve the understanding and independent character of the younger generation in the village of Siporas, Pinangsori District, Central Tapanuli Regency. As well as motivating them that education and entrepreneurship are two things that complement each other in order to create independent characters for the younger generation. Keywords: Independet character, Education, Enterpreneurship